KERJASAMA INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DAN PERKUMPULAN KELUARGA BERENCANA INDONESIA (PKBI) DALAM MELAKSANAKAN PROGRAM MENTAL HEALTH AND PSYCHOSOCIAL SUPPORT (MHPSS) TERHADAP PENGUNGSI DI PEKANBARU - Arief Wibowo; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
International Organization for Migration (IOM) works to help ensure the orderly and humane management of migration, to promote international cooperation on migration issues, to assist in the search for practical solutions to migration problems and provide humanitarian assistance to migrants in need, and has diverse activity on behalf of the well-being of refugees and also responsible to enlarge development, facilitating, and regulating migration. While Indonesian Planned Parenthood Association (IPPA) is a national NGO concerns to Sexual Reproductive Health and Rights (SRHR) education and services. The partnership of the two organizations with the diverse background able to collaborate and maintaining sustainable program to manage refugees who fled from internal conflict and persecution in their respective countries and have been placed in Pekanbaru City. This research using qualitative explanative as its method and collect the data by library research, interview with the stakeholders, and observation.This research elaborate a collaboration between IOM and IPPA in implementing a comprehensive program named Mental Health and Psychosocial Support (MHPSS) mainly aimed to recover mental health among refugees and sustaining a psychosocial education based on the program. MHPSS program started at 2017 to 2019 and has been implemented many activities with refugees in Pekanbaru as target beneficiaries and implemented comprehensive program. Keywords: International Organization for Migration, Indonesian Planned Parenthood Association, Mental Health and Psychosocial Support, Sexual Reproductive Health and Rights, refugees.